COMPETENCY-BASED IMPROVEMENT OF UNIVERSITY TRACK AND FIELD INSTRUCTION THROUGH DIGITAL-BIOMECHANICAL PEDAGOGY, INDIVIDUALIZED LOAD MANAGEMENT, AND DATA-INFORMED ASSESSMENT (American Journal of Interdisciplinary Research and Development, 2026)
This article theoretically and methodologically substantiates an integrated competency-based, digital-biomechanical, and load-monitored model for improving university track and field instruction. Its central claim is that effective athletics teaching cannot be reduced to routine drill repetition or the isolated use of technology; it must align technical structure, differentiated workload, augmented feedback, data-informed assessment, and reflective student participation within a single instructional architecture. The study develops a four-layer model applicable to sprint, jump, throw, and endurance units in mixed-ability higher-education cohorts. In this model, movement quality, functional adaptation, digital analysis, and pedagogical transfer are treated as interdependent rather than separate outcomes. The article demonstrates that such a design can reduce persistent technical errors, improve instructional individualization, strengthen students’ capacity for self-analysis, and shift evaluation from narrow normative testing toward multidimensional competence growth.